2013
DOI: 10.1016/j.jmbbm.2013.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue prediction in fibrin poly-ε-caprolactone macroporous scaffolds

Abstract: Tissue engineering applications rely on scaffolds that during its service life, either for in-vivo or in vitro applications, are under mechanical solicitations. The variation of the mechanical condition of the scaffold is strongly relevant for cell culture and has been scarcely addressed.Fatigue life cycle of poly-ε-caprolactone, PCL, scaffolds with and without fibrin as filler of the pore structure were characterized both dry and immersed in liquid water. It is observed that the there is a strong increase fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…This double porous structure results in and overall high porosity (83.4±2.6% 6 ) and has been previously proposed for cartilage and bone replacement [30][31][32] . Such structure favors scaffold permeability to nutrients and waste products of cell metabolism and can be used to retain active components 11,33,34 .…”
Section: Morphology Morphology Variation and Mechanical Responsementioning
confidence: 60%
See 3 more Smart Citations
“…This double porous structure results in and overall high porosity (83.4±2.6% 6 ) and has been previously proposed for cartilage and bone replacement [30][31][32] . Such structure favors scaffold permeability to nutrients and waste products of cell metabolism and can be used to retain active components 11,33,34 .…”
Section: Morphology Morphology Variation and Mechanical Responsementioning
confidence: 60%
“…However, accurate fitting to the Morrow´s energy model is just possible up to 200 loading-unloading cycles. The deviation for larger number of cycles occurs both for dry and pristine PCL 6 samples. This fact, should be related to complex changes in the porous structure and local interactions among the different phases (PCL, PVA and water).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A perfect elastomer does not show any hysteresis curve, the loading and unloading path are identical and no energy is dissipated (Love 1927) (Ewing 1889). In previous work (Panadero et al 2013) a macro and micro porous PCL scaffold was filled with a fibrin gel and mechanically tested for fatigue predictions up to 1 000 cycles. The hysteresis energy was calculated and with a mathematical model it was shown that filling the PCL scaffold with water or fibrin improved the fatigue life of the scaffold.…”
Section: Plastic Strain Energy Density (Hysteresis Energy)mentioning
confidence: 99%